Detection of Early Ischemic Changes with Virtual Noncontrast Dual-Energy CT in Acute Ischemic Stroke: A Noninferiority Analysis - Kauw, F.; Ding, V.Y.; Dankbaar, J.W.; van Ommen, F.; Zhu, G.; Boothroyd, D.B.; Wolman, D.N.; Molvin, L.; de Jong, H.W.A.M.; Kappelle, L.J.; Velthuis, B.K.; Heit, J.J.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Dual-energy virtual NCCT has the potential to replace conventional NCCT to detect early ischemic changes in acute ischemic stroke. In this study, we evaluated whether virtual NCCT is noninferior compared with standard linearly blended NCCT, a surrogate of conventional NCCT, regarding the detection of early ischemic changes with ASPECTS.MATERIALS AND METHODS: Adult patients who presented with suspected acute ischemic stroke and who underwent dual-energy NCCT and CTA and brain MR imaging within 48 hours were included. Standard linearly blended images were reconstructed to match a conventional NCCT. Virtual NCCT images were reconstructed from CTA. ASPECTS was evaluated on conventional NCCT, virtual NCCT, and DWI, which served as the reference standard. Agreement between CT assessments and the reference standard was evaluated with the Lin concordance correlation coefficient. Noninferiority was assessed with bootstrapped estimates of the differences in ASPECTS between conventional and virtual NCCT with 95% CIs.RESULTS: Of the 193 included patients, 100 patients (52%) had ischemia on DWI. Compared with the reference standard, the ASPECTS concordance correlation coefficient for conventional and virtual NCCT was 0.23 (95% CI, 0.15–0.32) and 0.44 (95% CI, 0.33–0.53), respectively. The difference in the concordance correlation coefficient between virtual and conventional NCCT was 0.20 (95% CI, 0.01–0.39) and did not cross the prespecified noninferiority margin of −0.10.CONCLUSIONS: Dual-energy virtual NCCT is noninferior compared with conventional NCCT for the detection of early ischemic changes with ASPECTS.CCCconcordance correlation coefficient